Effect and consequence of the rheological properties of nano Fe2O3-modified drilling muds in the Dibella oil field - Mahamadou, Abdoulaye seyni; Jun, Gu; Moctar, Maimouna Issa (Frontiers in Energy Research, 2024)
The development of supportable, cost-effective, and high-performance nanoparticles (NPs) is one of the new examination points within penetrating applications. The consideration of tailorable nanoparticles offers the chance to figure out water-based drilling fluids (WBDFs) with upgraded properties, providing exceptional opportunities in the energy, oil, gas, water, or framework enterprises. In WBDFs, nano and micron materials are investigated to control their rheological properties and their influence. This paper aims to analyze the influence of nano Fe2O3 on the rheological behavior of drilling fluid muds under high temperatures and pressure. Additionally, we seek to identify the optimal concentration of iron oxide nanoparticles that maintain consistent rheology; we examined the interfering effects of shear rates and iron oxide nanoparticle temperature on the shear type of the changed depleting liquid in the Dibella oil field to make the penetrating activity efficient, realistic, and skilled. We observe that as the temperature increases, the water-based mud (WBM), plastic viscosity (PV), yield point (YP), and gel strength (Gs) decrease until the reject structure is disrupted. Therefore, we must proceed with our assessment using nano Fe2O3 to resolve the shortcomings of the slope framework. Six water-based mud cakes containing 0.5, 1, 1.5, 2, 2.5, and 3 g weight percent of iron oxide (Fe2O3) nanoparticles were prepared for this evaluation. The experimental outcomes revealed an optimal nanoparticle mixing of 2.5 g weight percent, which resulted in a 13.8% reduction in the API filtrate volume and a 40% reduction in filter cake thickness. At 300°F temperature and type 10.00 pressure, the results of our experiments consistently demonstrate a decrease of 14.77% in the rheological properties of PV and YP and 10 s and 10 min in the gel strength of carbon oxide nanoparticles. The YP–PV span is 2.7, and the yield strength is 11 lb/100 ft2. On the other hand, mud cake A, which contains 0.5 wt% NPs, loses 6 mL of fluid after 30 min. In contrast, drilling mud cake E, which is composed of 3 wt% NPs, shows a fluid loss of 5.1 mL in the API filter press test. Based on the Bingham plastic model, the maximum shear stress versus shear rate was observed for bentonite drilling muds E and F, with 2.5 wt% and 3 wt% NPs, respectively, and this result indicates that the use of nano Fe2O3 can effectively adjust the properties of drilling fluids.